Resonance of awe - Keith, Julie Anne, author; Dormer, James T., advisor; Simons, Stephen R., advisor; Ellerby, David A., committee member; Harding, Blane, committee member (Colorado State University. Libraries, 2004)
My art is a visual expression of my intimate relationships to family and my surroundings. It is a search to unite the dichotomy of self and other, and a seeking out of the divine. Using landscape as subject matter I strive to create a visual vocabulary with line, shape, color, and movement to express a universal and spiritual way of seeing.
Keywords: printmaking, creating with the arts; Landscape art and architecture; Spirituality